Exploring ultrasound and electromyography for carpal tunnel syndrome diagnosis: a comprehensive comparative study and implications for occupational medicine - Braham, Salem; Moussa, Amen; Bouhoula, Marwa; Ben Meriem, Nihel; Annen, Ichraf; Sakly, Ghazi; Chouchane, Asma; Ben Abdelkader, Malek; Aloui, Asma; Kacem, Imène; Maoua, Maher; Kalboussi, Houda; et al. (Frontiers in Neurology, 2024)
BackgroundTo assess the contribution of ultrasound in diagnosing occupational carpal tunnel syndrome (CTS), compare it with electromyography (EMG) results, and evaluate the ultrasound characteristics of CTS patients.MethodsA nine-month cross-sectional study (January–September 2021) involved CTS patients and a control group, utilizing a structured form for data collection. EMG was performed on the patient group (‘cases’) and ultrasound examinations were conducted on both groups. Statistical analysis was performed using SPSS software.ResultsAmong 44 cases and 30 controls, CTS patients (mean age 44.9 years) exhibited predominantly bilateral symptoms (90.9%). The optimal cross-sectional area (CSA) threshold for diagnosis was 10.3 mm2 (89% sensitivity, 84% specificity). Significant differences in ultrasound criteria were observed between patient and control groups, including the “notch sign” (p = 0.012), hypoechoic appearance (p = 0.016), and reduced median nerve mobility (p = 0.021). Quantitatively, CSA (13.7 mm2 vs. 7.4 mm2), flattening ratio (3.3 vs. 2.1), and retinaculum bulging (3.2 mm vs. 1.9 mm) significantly differed between cases and controls (p = 0.0019, 0.025, and 0.01, respectively). Positive Phalen tests correlated with higher CSA (p = 0.005) and retinacular bulging (p = 0.02). CSA correlated with EMG parameters, indicating slower conduction velocities, lower amplitudes, and longer latencies (p < 10^(−3), r = −0.56, −0.62, −0.36, and −0.68, respectively).ConclusionThis study highlights ultrasound’s diagnostic potential for CTS, particularly in occupational settings. Its non-invasiveness and reliability advocate for its integration into routine diagnostic protocols, supporting evidence-based management strategies. Further research is needed to explore long-term efficacy and broader applicability.